Osteoclast-like giant cells in hepatocellular carcinoma case description and review of the literature. Issue 2 (4th March 2023) - Gielen, Anke H. C.; Samarska, Iryna; Den Dulk, Marcel; Beckervordersandforth, Jan; Dejong, Kees H. C.; Bouwense, Stefan A. W.; Dewulf, Maxime
Abstract: Background: The presence of osteoclast-like giant cells (OGC) in hepatocellular carcinoma (HCC) is rare and literature on this topic is scarce. In this article, we report on a case of a 77-year-old male patient with HCC with OGC and provide an overview of the current literature. Methods: We conducted a systematic search to find all available literature on OGC in HCC. The electronic databases PubMed, Web of Science, Embase and CENTRAL were searched from inception until October 2020. Results: Thirteen articles on this topic were identified and were included in this review. Data on 14 patients were available, described in twelve case reports, one patient in a patient series and the present case. Median age of included patients was 68 years. Two patients underwent neoadjuvant therapy prior to surgery. Of the 14 cases, eight tumours with OGC arose in a cirrhotic liver. Oncological outcome in this series was unfavourable, even after surgical resection, with a median disease-free survival of 75 d. Conclusions: The presence of OGC in HCC is rare. Current literature is scarce, and suggests an unfavourable outcome in regard to overall survival of HCC.